IMPLEMENTASI PENDIDIKAN KARAKTER TERHADAP KARAKTER SISWA DI SEKOLAH MENENGAH KEJURUAN BETHEL PETAMBURAN - Erita Dewi Sirait; Sadrakh Sugiono (Edukasi : Jurnal Pendidikan Agama Kristen, 2020)
Starting from the author observing the behavior of adolescents nowadays, their behavior is increasingly deteriorating. Such as the increase in promiscuity, crimes against others, cheating habits, abuse of drugs, pornography, and others. Based on the researchers' observations and some of the information obtained, there were some students who were impolite in their words and actions towards fellow students, teachers, and parents. Cheating, breaking the rules was also done by some of the students at SMK Bethel Petamburan, Central Jakarta. This is a deviant action to continue to be applied because it will form character in students. For this reason, the authors conducted research with an indication that character education at SMK Bethel Petamburan, Central Jakarta, has not been maximally implemented to form student character, so there are still students who show bad character. And with the title: The Impact of the Implementation of Character Education on the Character of Students at SMK Bethel Petamburan, Central Jakarta. The hypothesis proposed is to measure how much influence the implementation of character education applied by schools to the character of children at SMK Bethel Petamburan, Central Jakarta. The conclusion obtained by the author is that the effect of the implementation of character education implemented by schools on the character of students at SMK Bethel, Central Jakarta is 32.8% and the rest is influenced by other factors (namely, internal factors, external factors, and developmental factors at the age of 15-17 years).